The development of novel pterin chemistry leading to potential dihydrofolate reductase inhibitors with potential antimalarial activity - Nxumalo, Winston (My University, 2012)
This thesis describes the application pteridine chemistry in various aspects of methodology development and natural product synthesis. The introductory chapter sets the scene by describing naturally occurring pteridines, their applications in biological systems, and recent synthetic strategies. Firstly, Sonogashira coupling reactions employing benzenesulfonyloxy-O-pteridine (27) and terminal alkynes to give various 6-substituted pteridines are described. This methodology allowed for the total synthesis of a natural occurring pteridine, Sepiapterin-C (46). Negishi coupling reactions involving benzenesulfonyloxy-O-pteridine (27) and various Znreagents are also reported. This methodology, representing the first Negishi coupling on a pteridine nucleus, allowed for the introduction of both aryl- and heteroaryl- substituents at the 6- position of the pteridine ring. The use of methanesulfonyloxy-O-pteridine (26) as a coupling partner is also described. Selective deprotection and hydrolysis of the formamidine protecting groups to give either the 6- substituted 2,4-diaminopterine or 2-amino-4-oxo-pteridine (pterin), is described. The synthesized structures are supported by NMR and mass spectral data and melting points where applicable. Novel compounds are verified by NMR spectroscopy, infrared and mass spectrometry.
Ph.D., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Enzyme inhibitors; Pyrimidines; Pteridines; Chemistry, Organic